Temporal asymmetry in activation of Aplysia adenylyl cyclase by calcium and transmitter may explain temporal requirements of conditioning. - Yovell, Y (1992)
Cellular experiments have suggested that during classical conditioning of the gill and siphon withdrawal reflex of Aplysia, adenylyl cyclase may serve as a molecular site of convergence for Ca2+ and serotonin (5-hydroxytryptamine; 5-HT), the cellular representations of the conditioned and unconditioned stimuli (CS and US). We explored the possible molecular basis of the behavioral requirement that the CS and US be paired within a narrow time window and in the appropriate order. To examine the temporal interactions of brief pulses of Ca2+ and 5-HT in stimulating Aplysia neural cyclase, we used a perfused-membrane cyclase assay. When brief pulses of Ca2+ and 5-HT were paired, cyclase activation depended upon the sequence of the pulses: peak cyclase activation was greater when the Ca2+ pulse immediately preceded the 5-HT pulse. Examination of the rising phase of 5-HT stimulation suggested that a Ca2+ prepulse might accelerate the onset of activation by 5-HT, without affecting the final level of activation achieved with prolonged 5-HT exposure. The observed interactions between Ca2+ and transmitter in activating cyclase could contribute importantly to the temporal requirements of conditioning for CS-US pairing.